Sodium intake by hyperosmotic rats treated with a GABAA receptor agonist into the lateral parabrachial nucleus. - Kimura, Everton Heidi (2008)
Inhibitory mechanisms in the lateral parabrachial nucleus (LPBN) and central GABAergic mechanisms are involved in the regulation of water and NaCl intake. Besides increasing fluid depletion-induced sodium intake, the activation of GABAA receptors with muscimol into the LPBN also induces ingestion of 0.3 M NaCl in normonatremic, euhydrated rats. It has been suggested that inhibitory mechanisms activated by osmotic signals are blocked by GABAA receptor activation in the LPBN, thereby increasing hypertonic NaCl intake. Therefore, in the present study we investigated the effects of muscimol injected into the LPBN on water and 0.3MNaCl intake in hyperosmotic cell-dehydrated rats (rats treated with an intragastric load of 2 M NaCl). Male Wistar rats with stainless steel cannulas implanted bilaterally into the LPBN were used. In euhydrated rats, muscimol (0.5 nmol/0.2 μl), bilaterally injected into the LPBN, induced ingestion of 0.3 M NaCl (24.6±7.9 vs. vehicle: 0.5±0.3 ml/180 min) and water (6.3±2.1 vs. vehicle: 0.5±0.3 ml/180 min). One hour after intragastric 2 M NaCl load (2 ml), bilateral injections of muscimol into the LPBN also induced 0.3 M NaCl intake (22.1±5.2 vs. vehicle: 0.9±0.8 ml/210 min) and water intake (16.5±3.6 vs. vehicle: 7.8±1.8 ml/210 min). The GABAA antagonist bicuculline (0.4 nmol/0.2 μl) into the LPBN reduced the effect of muscimol on 0.3MNaCl intake (7.1±2.1 ml/210 min). Therefore, the activation ofGABAA receptors in the LPBN induces ingestion of 0.3 M NaCl by hyperosmotic cell-dehydrated rats, suggesting that plasma levels of renin or osmolarity do not affect sodium intake after the blockade of LPBN inhibitory mechanisms with muscimol.